2014
DOI: 10.1111/wbm.12055
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect impacts of different water regimes on the invasive plant, alligator weed (Alternanthera philoxeroides), and its biological control agent, Agasicles hygrophila

Abstract: Invasive weeds are broadly affected by natural disturbances, such as flooding and drought. While these disturbances can directly affect the outcome of a plant invasion, they can also indirectly affect the population dynamics of the invasive plant's natural enemies. However, how flooding and drought alter the interactions of invasive plants with their natural enemies and what impact these events have on the invasive plants have been little studied. This study reports on the effects of flooding and drought on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Drought indirectly affects the growth, development, population reproduction and other biological characteristics of natural predators 27,33,34 . Drought has been reported to have negative impacts on the population of natural predators, such as reducing the survival rate of Meteorus pulchricornis (Wesmael) and lowering the longevity and fecundity of Anagrus nilaparvatae 41–43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drought indirectly affects the growth, development, population reproduction and other biological characteristics of natural predators 27,33,34 . Drought has been reported to have negative impacts on the population of natural predators, such as reducing the survival rate of Meteorus pulchricornis (Wesmael) and lowering the longevity and fecundity of Anagrus nilaparvatae 41–43 .…”
Section: Discussionmentioning
confidence: 99%
“…32 Drought may also indirectly affect the growth and reproduction of natural predator populations. 27,33,34 For example, drought reduced the parasitic rate of Aphidius ervi. 35 However, this effect may also be beneficial; for instance, drought increased the parasitic rate of the natural parasitoids of Stephensia brunnichella.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Allen et al (2014) reported that changing environmental temperature may create constraints on reproduction and development of Cyrtobagous salviniae, BCA of Salvinia molesta. Wei et al (2015) also studied about the effect of different water regimes on Agasicles hygrophila, BCA of Alternanthera philoxeroides and suggested that drought can reduce the biological control of weed indirectly by interfering with plant-insect interaction.…”
Section: Effect On Weed Managementmentioning
confidence: 99%
“…Alligator weed can also cause the death of fish and native plants and provides a favorable habitat for mosquitoes (Bhattacherjee et al 2014). The control and elimination of AP includes biological (Sun et al 2010;Wei et al 2015), chemical, and physical methods (Schooler et al 2008). Biological control is a valuable and environmentally friendly method of weed control.…”
Section: Introductionmentioning
confidence: 99%